PENGARUH SIKAP DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA SISWA - Asep Munawar; Nono Supriatna (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2018)
This study aims to examine the influence of attitudes and motivation on student entrepreneurship interests, research methods used survey with quantitative approach, using a sample of 60 students of SMAN 3 Purwakarta. Data analysis technique used is Factor Analysis, Multiple Regression Analysis, and One Way Anova. The result of the research shows that the attitude has a significant effect on the entrepreneurship interest of the students, or has a significant role to the establishment of entrepreneurship interest in the students, and the motivation has a significant effect on the entrepreneurship interest of the student or has a role to the student entrepreneur interest. motivation has a significant effect on student entrepreneur interest. This shows that attitudes and motivations will provide an indirect experience to a person to have an entrepreneurial interest, because at least a person or a student has the knowledge of how to run a business, how to deal with problems in a business, how to market a product or service, how to access capital and etc.